Storage modeling standard Cr(VI) solution based on comparison of time regression value with UV-Vis spectrophotometry - FACHRURRAZIE; Elfiwani (UNIB Press, 2022)
Chromium (Cr) compounds are found in nature in two forms, Cr (III) and Cr (VI). Analysis of Cr (VI) was determined using spectrophotometer UV-vis. A standard solution must be fresh as a standard that is usually not used repeatedly in the measurement. This study aims to determine whether the standard solution of Cr (VI) be used for a certain period until it must be disposed of. This idea is based on Cr (VI) compounds that were categorized as hazardous and toxic materials. In this study, the shelf life of standard Cr (VI) was carried out with controlled temperature and humidity in a refrigerator at 4 ℃ during the test period of two days. In this study, there was found that every hour of storage of standard Cr (VI) will observe a change in the gradient value of the regression. The model then compared with p-value resulted in only up to 7 hours of storage with a deviation of regression slope and intercept compared with initial time (T0–T7) is 0.0062 and 0.0019 which and its increases over time. From the result, it can be concluded that standard regression can be used as a model for determining the maximum storage time by comparing the regression values each time so that the seven hours storage time is the limit where the Cr (VI) that can no longer be used as a measurement standard. It concerned that standard regression could be used as a model for determining the maximum storage time by comparing the regression values each time. Keywords: Cr (VI), Modeling, Regression, Spectrophotometry UV-vis, T-Test